Development of a new method for the detection and quantification of octopamine and 3-nitrotyrosine - Teixeira, Dulce (2018)
Neurodegenerative diseases affect around 30 million people worldwide, thus new methods that can facilitate research of such diseases are essential. Neurotransmitters, characterised as critical regulators of several neurological disorders, have been the target for the development of such methods. Besides, oxidative/ nitrosative stress has been associated with several neurodegenerative diseases and is thought to play an important role in their pathogenesis. Therefore, the development of bioanalytical methods for quantification of neurotransmitters and oxidative stress-associated molecules seems to be an interesting approach. The aim of this study was to develop a simple, rapid, low-cost and sensitive octopamine (OCT) and 3-nitrotyrosine (3-NT) quantification method for use in biological models.